The The Development of Digital Accounting Information System Implementation among SMEs in Indonesia - Mukhtar (Management Science Research Journal, 2025)
Digital technology development has transformed the business landscape, particularly for Micro and Small Enterprises (MSEs), where Digital Accounting Information Systems (AIS) have become a critical tool. Digital AIS enhances operational efficiency, financial planning, and marketing, ultimately impacting revenue growth, with entrepreneur education being a crucial factor for successful adoption. This descriptive quantitative study aims to analyze the relationship and correlation direction between the implementation of digital AIS and the characteristics of SMEs in Indonesia. It utilizes panel data from the 2011-2023 SME profile surveys issued by Statistics Indonesia (BPS) and data on accounting software available on the Play Store. The indicators for SME characteristics are business capital, revenue, marketing, and education. The indicators for accounting software are rating, reviews, and downloads. The data were analyzed using Spearman’s non-parametric statistical test. The results indicate a significant correlation between Digital AIS adoption and business capital and marketing, but no significant correlation with revenue and education. These findings underscore the necessity to develop and promote a holistic, context-based AIS implementation model. This model should be designed with user-friendly, integrated features and support certification programs for SMEs that demonstrate high-quality AIS implementation. Keywords: Business Capital, Marketing Revenue, Education, Digital Accounting Information System (AIS)